A Study on Purchase Intent Drivers and Empowerment of Women by Micro Finance Institutions - Mansurali, Anifa; Swaminathan, R (Journal of Contemporary Research in Management (JCRM), 2017)
Micro Finance Institutions (MFIs) are aimed at achieving the goal of ‘freedom from poverty’ by enhancing the livelihood and well-being of economically poor population around the world. MFI provide financial assistance services through loan, savings schemes, insurance, and money transfers to the Bottom of pyramid segment of the countries wherever they operate. Nobel Laureate Mohammed Yunus and Prahalad C K with their continuous efforts have contributed significantly for the development of this field. Their contributions made MFIs profitable by serving the poor and the low income people ‘worthy to credit’. The report from World Bank (2012) stated that by the year 2015, 23.6 percentage of the world population would be striving to survive with as low as 1.25 per day, and this report set the pathway for a large number of corporate and social entrepreneurs to look upon MFI a panacea to World’s poverty. Among the poor, the female gender has proved to be highly vulnerable (poorer) due to the disempowerment and low education in most countries of the world. At the same time, MFIs believed that women are more trustworthy and enterprising than men due to the social status and peer pressure for income. Hence, most MFI in developing nations have only women clienteles and perhaps this proved to be a successful model in the past two decades. Women became empowered, educated, entrepreneurs and improved the society’s living standard through MFI. This study is descriptive by nature and one of the pioneering efforts to understand the purchase intent drivers of MFI. The study was conducted during 2012-2016 in the state of Tamil Nadu, India; TN is the second largest market for MFI operations in the country. 736 samples were drawn from select thirteen districts of TN with the logical basis of most intervened and less intervened MFI services. The research focused into the new domain to observe the consumption pattern and poverty scorecard of MFI clients. The practical indifferences between the members and non-members of MFI were also brought into light through this study. The study also recommends certain specific policy and regulatory changes for the betterment of both MFI and rural poor. At the estimate, the research also establishes the opportunities for MFI to involve into a bigger role in transforming the life of rural poor towards prosperity